PENGARUH SERVANT LEADERSHIP DAN BUDAYA ORGANISASI SEKOLAH TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH ATAS NEGERI DI KOTA PADANG - Fitrah Santosa; Adrianto Adrianto; Syamsir Syamsir; Afriva Khaidir (STKIP Pesisir Selatan, 2019)
The objectives of this study were: 1) to determine the effect of servant leadership on teacher performance in state senior high schools in the city of Padang. 2) to determine the effect of school organizational culture on teacher performance in state senior high schools in the city of Padang . This study used an associative quantitative method, the population of this study were all state senior high school teachers in the city of Padang, with a sample of 292 teachers. Analysis of the data used in this study is a regression analysis technique, in addition, the researchers also used descriptive analysis to obtain a descriptive measurement from each research variables. The results of this study are: 1) servant leadership has a positive and significant effect on teacher performance in State Senior High Schools in the City of Padang. 2) school organizational culture has a positive and significant effect on teacher performance in State Senior High Schools in the city of Padang